2008
DOI: 10.1080/17450390802066435
|View full text |Cite
|
Sign up to set email alerts
|

On the effects of the concentrate proportion of dairy cow rations in the presence and absence of aFusariumtoxin-contaminated triticale on cow performance

Abstract: The aim of the present study was to investigate the effects of a deoxynivalenol (DON) contaminated ration with a concentrate proportion of 50%, on the performance of dairy cows (Period 1), and to examine the effects when the concentrate proportion was elevated to 60% compared to a ration with 30% concentrates (Period 2). In Period 1, 13 lactating German Holstein cows (Myco group, on average 29 days in milk) were fed the experimental diet (on average 5.3 mg DON/kg DM) as total mixed ration over 11 weeks, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 36 publications
2
35
1
Order By: Relevance
“…The daily dry matter intake amounted to 17.4 kg DM and varied between 16.1 and 18.3 kg/day. The feed intake was consistent with a previous experiment carried out at the experimental station of the FLI (Keese et al 2008). The mean energy intake in the present study was 119 MJ NEL/day, which indicates an adequate energy supply of the animals during the entire experiment (GfE 2001).…”
Section: Feed Intake and Milk Yieldsupporting
confidence: 77%
“…The daily dry matter intake amounted to 17.4 kg DM and varied between 16.1 and 18.3 kg/day. The feed intake was consistent with a previous experiment carried out at the experimental station of the FLI (Keese et al 2008). The mean energy intake in the present study was 119 MJ NEL/day, which indicates an adequate energy supply of the animals during the entire experiment (GfE 2001).…”
Section: Feed Intake and Milk Yieldsupporting
confidence: 77%
“…The slightly fluctuant DOM-1 concentrations in the serum of the control cows reflected the variability in the DON concentrations in the used maize silages. Furthermore the time-dependent course corresponds to the time-dependent course of the total DM intake (shown at Keese et al [22]). …”
Section: Don Intakementioning
confidence: 96%
“…During the 29 wk of the current trial we observed some cases of clinical mastitis in individual cows but we could not detect an obvious relation between the occurrence of clinical signs of an udder infection and elevated DOM-1 concentrations in milk samples of the affected cows. Anyway it has to be stressed that cows showing clinical signs of mastitis were treated immediately and that the determination of the somatic cell count was just adequate to get an impression about the udder health of the animals in this study for the reasons discussed by Keese et al [22].…”
Section: General Aspects Of Residues In Serum Milk and Bilementioning
confidence: 98%
See 2 more Smart Citations